FORCED TRANSITION INTO ONLINE ASSESSMENTS: EXPLORING PERCEPTIONS AND CHALLENGES AMONGST PHARMACY STUDENTS - Mohd Izani Othman,; Mohd Nadzri Mohd Najib,; Suraya Sulaiman, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
In the wake of COVID-19 pandemic, most educational activities have been forced to resumed through online and distance learning. As part of the curriculum objectives, online assessments are carried out to assess students' comprehension and to evaluate the effectiveness and quality of the teaching and learning process. Many students were heavily affected by these sudden transformations from traditional face-to-face (F2F) to forced online assessments. Thus, making it intriguing for academics to explore students' experiences of online assessment at the higher education level. Our study investigates students’ perceptions and challenges faced of online assessments. A cross-sectional study was conducted by distributing questionnaire to pharmacy students at Universiti Teknologi MARA (UiTM), Kampus Bertam through online Google Form. Data obtained from the questionnaire which consisted of demographic information, perceptions and challenges of online assessments were tabulated and analysed using Microsoft Excel and SPSS. Our findings on perceptions revealed that online assessments were conducted in many ways (92.3%) and using multiple platforms (91.6%). Online assessments enhanced self-learning (89.5%), convenient and flexible (86.0%) and faster compared to paper assessments (78.3%). Nevertheless, respondents stated that online assessments are neither applicable for all courses (70.6%) nor for all students (60.8%) whilst 86.7% of respondents stated the vulnerability of online assessments to cheating. Likewise, most students indicated distractions at home or from others (86.0%) as the challenge of online assessments followed by difficulties in answering questions within time limit (76.9%), lack of motivation (75.5%) and do not have enough time to check all answers (72.7%). Suggestions from respondents to improve online assessment approaches include allocating more time during assessment, increase engagement and feedback between students and lecturers and tighten up security to prevent students from dishonesty. In general, the study illustrates the acceptance and the constructive approach of online assessments amongst students. Though, the challenges encountered need to be acknowledged and resolved accordingly.